To simplify the expression \( \frac{5a^4b^2c}{a^3b} \), we can break it down as follows:
-
Divide the coefficients: The coefficient in the numerator is 5 and in the denominator is 1, so it remains 5.
-
Simplify the \( a \) terms: \[ \frac{a^4}{a^3} = a^{4-3} = a^1 = a \]
-
Simplify the \( b \) terms: \[ \frac{b^2}{b^1} = b^{2-1} = b^1 = b \]
-
The \( c \) term: Since there are no \( c \) terms in the denominator, it remains \( c^1 \).
Putting this all together, we have: \[ \frac{5a^4b^2c}{a^3b} = 5a^1b^1c^1 = 5abc \]
In this expression, the exponent of \( c \) is \( 1 \).
Thus, the simplified exponent of \( c \) in the expression is 1.